ANALISA PENGGUNAAN APLIKASI PENDUKUNG PEMBELAJARAN DARING DI PAUD PADA MASA PANDEMI COVID-19 - Afifah, Alfiah Nur; Widayati, Sri; Reza, Muhammad; Ningrum, Mallevi Agustin; Nisa, Aliyatun (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2022)
This research is based on a change in teaching patterns from face-to-face to online caused by the Covid-19 pandemic. This study uses a quantitative approach with a descriptive method which aims to determine the perception of PAUD teachers regarding the applications used during online learning during the Covid-19 pandemic. The subjects of this study were PAUD teachers totaling 126 respondents in the city of Surabaya. This research is quantitative research using quantitative descriptive data analysis techniques. The data collection technique in this study used a survey method in the form of a questionnaire in the form of a Google Form. From the data of this study, it was found that most PAUD teachers in Surabaya more often use the WhatsApp application to carry out online learning. When using the application, teachers often experience major problems related to the network. Even so, most PAUD teachers in Surabaya agree that the benefits of using the application are that the application is very effective and efficient to use in carrying out teaching and learning activities during the pandemic.